Bilateral cochlear implants with large asymmetries in electrode insertion depth: implications for the study of auditory plasticity. (April 2015) - Svirsky, Mario A.; Fitzgerald, Matthew B.; Sagi, Elad; Glassman, E. Katelyn
Abstract: Conclusion: The human frequency-to-place map may be modified by experience, even in adult listeners. However, such plasticity has limitations. Knowledge of the extent and the limitations of human auditory plasticity can help optimize parameter settings in users of auditory prostheses. Objectives: To what extent can adults adapt to sharply different frequency-to-place maps across ears? This question was investigated in two bilateral cochlear implant users who had a full electrode insertion in one ear, a much shallower insertion in the other ear, and standard frequency-to-electrode maps in both ears. Methods: Three methods were used to assess adaptation to the frequency-to-electrode maps in each ear: (1) pitch matching of electrodes in opposite ears, (2) listener-driven selection of the most intelligible frequency-to-electrode map, and (3) speech perception tests. Based on these measurements, one subject was fitted with an alternative frequency-to-electrode map, which sought to compensate for her incomplete adaptation to the standard frequency-to-electrode map. Results: Both listeners showed remarkable ability to adapt, but such adaptation remained incomplete for the ear with the shallower electrode insertion, even after extended experience. The alternative frequency-to-electrode map that was tested resulted in substantial increases in speech perception for one subject in the short insertion ear.